Essentials of a new clinical practice guidance on familial hypercholesterolaemia for physicians. Issue 5 (27th May 2021) - Watts, Gerald F.; Sullivan, David R.; Hare, David L.; Kostner, Karam M.; Horton, Ari E.; Bell, Damon A.; Brett, Tom; Trent, Ronald J.; Poplawski, Nicola K.; Martin, Andrew C.; Srinivasan, Shubha; Justo, Robert N.; et al.
Abstract: Familial hypercholesterolaemia (FH) is a common, heritable and preventable cause of premature coronary artery disease. New clinical practice recommendations are presented to assist practitioners in enhancing the care of all patients with FH. Core recommendations are made on the detection, diagnosis, assessment and management of adults, children and adolescents with FH. Management is under‐pinned by the precepts of risk stratification, adherence to healthy lifestyles, treatment of non‐cholesterol risk factors and appropriate use of low‐density lipoprotein (LDL)‐cholesterol‐lowering therapies including statins, ezetimibe and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. The recommendations need to be utilised using judicious clinical judgement and shared decision‐making with patients and families. New government‐funded schemes for genetic testing and use of PCSK9 inhibitors, as well as the National Health Genomics Policy Framework, will enable adoption of the recommendations. However, a comprehensive implementation science and practice strategy is required to ensure that the guidance translates into benefit for all families with FH.